2019
DOI: 10.15294/ujph.v0i0.29527
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Having an Autistic Child in Malay Family Indonesia

Abstract: The condition of families with autistic children raises many views and judgments both from family and society. This ethnographic study aimed to describe the meaning of families and communities towards families with autistic children. Data were collected through focus group discussions and in-depth interviews. Key informants come from families who have autistic children and community members recruited by purposive sampling, while the data were analyzed using thematic analysis. This study results generate  two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…Kehadiran anak ASD dalam keluarga dapat berdampak bagi kehidupan. Beberapa aspek yang terdampak diantaranya aspek emosional, fisik, ekonomi, pekerjaan, dan hubungan keluarga (Jiu & Rungreangkulkij, 2019). Beberapa dampak tadi membuat ibu memunculkan rasa yakin dalam menyelesaikan masalah.…”
Section: Pendahuluanunclassified
“…Kehadiran anak ASD dalam keluarga dapat berdampak bagi kehidupan. Beberapa aspek yang terdampak diantaranya aspek emosional, fisik, ekonomi, pekerjaan, dan hubungan keluarga (Jiu & Rungreangkulkij, 2019). Beberapa dampak tadi membuat ibu memunculkan rasa yakin dalam menyelesaikan masalah.…”
Section: Pendahuluanunclassified
“…Karakteristik profesi orang tua dalam penelitian ini menunjukkan mayoritas memilih menjadi ibu rumah tangga, namun ada juga yang tidak memenuhi kriteria orang tua. Hasil studi tahun 2019 oleh Jiu dan Rungreangkulkij menjelaskan bahwa perempuan adalah pengasuh utama anak di rumah, itulah sebabnya beberapa ibu ingin berhenti bekerja dan merawat anak ASD mereka (Jiu and Rungreangkulkij, 2019). Menurut peneliti, setiap keluarga, apapun profesi orang tuanya, berisiko memiliki anak dengan ASD.…”
Section: Hubungan Pola Asuh Dengan Perkembangan Bhasa Reseptif Pada A...unclassified
“…In a study of the diagnosis of ASD in urban Indonesia (Sidjaja et al., 2017), it was identified that a key challenge in effective diagnoses of ASD is a lack of trained practitioners as well as validated, translated, culturally appropriate assessment tools. A qualitative study documenting the meaning of having a child with autism for indigenous Malay families and communities noted the importance for health professionals to consider key things in their work (Jiu & Rungreangkulji, 2019). Key themes highlighted notions of a child with autism being both a “test” and “destiny” from God, and that children with autism require “extra helping” and have different needs than neurotypical children (Jiu & Rungreangkulji, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study documenting the meaning of having a child with autism for indigenous Malay families and communities noted the importance for health professionals to consider key things in their work (Jiu & Rungreangkulji, 2019). Key themes highlighted notions of a child with autism being both a “test” and “destiny” from God, and that children with autism require “extra helping” and have different needs than neurotypical children (Jiu & Rungreangkulji, 2019). Additionally, a study of six mothers of children with ID in West Sumatra (Merianti et al., 2019) identified themes of anxiety and worry about the future of the child, and financial constraints impacting the ability to access education and adequate care.…”
Section: Introductionmentioning
confidence: 99%